2017
DOI: 10.1038/s41598-017-15325-5
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of healthy and cancerous tissues in 2D and 3D

Abstract: Metabolism is a compartmentalized process, and it is apparent in studying cancer that tumors, like normal tissues, demonstrate metabolic cooperation between different cell types. Metabolic profiling of cells in 2D culture systems often fails to reflect the metabolism occurring within tissues in vivo due to lack of other cell types and 3D interaction. We designed a tooling and methodology to metabolically profile and compare 2D cultures with cancer cell spheroids, and microtissue slices from tumors, and normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 46 publications
2
79
0
Order By: Relevance
“…Metabolic profiling is used to demonstrate metabolic cooperation between varying cell types and is becoming a popular technique in 3D culture models due to the accuracy of the results when compared to cells in vivo (Tung et al, 2011). Previously, 2D culture models have been used to test cancer metabolism but recent studies suggest 3D culture models provide more insight when testing the efficacy of new drugs (Russell et al, 2017). Through profiling, researchers have discovered that drug treatments sometimes kill all the cells in 2D culture monolayer but only kill some of cells that make-up the protective layer of spheroids in 3D models (Russell et al, 2017).…”
Section: Cell Culture For Drug Discoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic profiling is used to demonstrate metabolic cooperation between varying cell types and is becoming a popular technique in 3D culture models due to the accuracy of the results when compared to cells in vivo (Tung et al, 2011). Previously, 2D culture models have been used to test cancer metabolism but recent studies suggest 3D culture models provide more insight when testing the efficacy of new drugs (Russell et al, 2017). Through profiling, researchers have discovered that drug treatments sometimes kill all the cells in 2D culture monolayer but only kill some of cells that make-up the protective layer of spheroids in 3D models (Russell et al, 2017).…”
Section: Cell Culture For Drug Discoverymentioning
confidence: 99%
“…Previously, 2D culture models have been used to test cancer metabolism but recent studies suggest 3D culture models provide more insight when testing the efficacy of new drugs (Russell et al, 2017). Through profiling, researchers have discovered that drug treatments sometimes kill all the cells in 2D culture monolayer but only kill some of cells that make-up the protective layer of spheroids in 3D models (Russell et al, 2017). The extra dimension in 3D culture has helped researchers understand the flaws present in 2D models that cause lower rates of drug efficacy relative to in vivo trials (Ferrick et al, 2008).…”
Section: Cell Culture For Drug Discoverymentioning
confidence: 99%
“…Cells in a 3D environment behave fundamentally differently from cells in monolayer culture . The spheroid formation causes resistance to anti–cancer drugs and metabolic heterogeneity in cultured cell lines of CRC. To investigate whether the relationship between the malignancy of CRC and the expression pattern of metabolic enzymes exists in cultured cells, we performed 3D sphere culture of HCT116 CRC cells.…”
Section: Resultsmentioning
confidence: 99%
“…A fourth Calu- 6 xenograft cohort was used separate to those used for MRI and pathology analysis. Tissue biopsy preparation protocols were adapted from a previously published method (19) and are described in Supplementary Methods. Separate mouse cohorts were used: Calu-6 xenograft groups were time-matched control (N ¼ 7), size-matched control (N ¼ 5), and treated with single 10 Gy fraction of radiotherapy (N ¼ 6) ( Supplementary Fig.…”
Section: Xenograft Oxygen Consumption Rate Analysismentioning
confidence: 99%
“…Because previous work (19) has shown that percentage viability and necrotic fraction of tumors is directly proportional to observed oxygen consumption, we used hematoxylin and eosin (H&E) staining to quantify necrotic fraction for each sample using a scoring method based on the level of nuclear staining. Following OCR measurements, the samples were imaged using Oxford Optronix GelCount (Oxford Optronix Ltd.).…”
Section: Xenograft Oxygen Consumption Rate Analysismentioning
confidence: 99%